Kedudukan Surat Keputusan Bersama sebagai Pedoman Implementasi Pasal Penghinaan dan Pencemaran Nama Baik dalam UU ITE - Ramadhani, Defi Sri Sunardi; Noerdajasakti, Setiawan; Sulistio, Faizin (Universitas Negeri Malang, 2022)
This study aimed to analyze the guidelines for implementing Article 27 paragraph (3) of Electronic Transaction and Information Law and the joint decree's legal standing as guidelines for implementing the law on information and electronic transactions. This study utilized a normative juridical method with a historical approach, a conceptual approach, and a statutory approach. The implementation of Article 27 paragraph (3) of Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 was based on the Decision of the Constitutional Court Number 50/PUU-VI/2008 that referred to Article 310, Article 311, and Article 315 of the Indonesian Criminal Act. Although it was not explicitly stated in Article 7 paragraph (1) of Law Number 12 of 2011 concerning the Establishment of Legislation, the joint decree as guidelines for implementing the law on information and electronic transactions had the same position and binding legal force as the laws and regulations.